Social Attitudes Towards Women Entrepreneurs in Algeria - Boufeldja Ghiat (Journal of Management Practices, Humanities and Social Sciences, 2017)
The aim of the study is to investigate the impact of social attitudes on women entrepreneurs in Algerian environment. The main obstacle for women entrepreneurs in Algeria is that entrepreneurship was reserved for males, therefore, considered as a male occupation. To be entrepreneurs, women have to face negative reactions and pressures from society: the family, the neighbours, men, and even females. Several people, including females, do not accept to work under the supervision of women. In order to shed light on this problem, a questionnaire was used for the collection of data, and filled in by a sample of 30 randomly chosen women entrepreneurs. Means and percentages of answers were computed. Social attitudes were found to be the source of constraints and cause problems for women entrepreneurs in Algeria. Results from this research can be used by decision-makers in making the right decisions for the benefit of women entrepreneurship in the Middle East and North Africa.